Effect of casein-chitosan edible coating on the Physicochemical and microbiological characteristics of broiler meat at storage 8° C - Mulia Winirsya Apriliyani; Abdul Manab; Premy Puspitawati Rahayu; Miftahul Jannah; Puput Nurul Hidayah; Fina Faleha Firdiatila (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2021)
Microbial contamination and fat oxidation may cause physical and chemical changes that can reduce the quality of broiler meat. The objective of this study was to determine the ability of casein chitosan edible coatings in maintaining the quality of broiler meat stored in certain storage time under refrigeration (8 oC), in terms of water activity (Aw), cooking loss, organoleptic properties (i.e. color, aroma and possible deviations), physicochemical properties (i.e. moisture content, water holding capacity/WHC, pH, lipid content, color), Total Plate Count (TPC), and microbial properties (i.e. Staphylococcus aureus, Escherichia coli, and Salmonella sp.). The materials used were broiler breast fillets and casein chitosan edible coating. The research was conducted using a Completely Randomized Design (CRD) based on 5 variations in storage time treatments i.e. at 0 h; 24 h; 72 h; 120 h; and 168 h in 4 replications. Edible coating casein chitosan on broiler meat under storage showed significant on Aw, WHC, pH, lightness, TPC, S. aureus, and E. coli. The application of casein-chitosan as an edible coating could be suitable to assure the safety of food products such as chicken meat at the range of storage time studied.